Burden of Chickenpox on Families: A Study in Quebec - Philippe De Wals; Manon Blackburn; Maryse Guay; Gina Bravo; Danièle Blanchette; Monique Douville-Fradet (Canadian Journal of Infectious Diseases)
OBJECTIVE: To estimate the nonhospital costs of treating chickenpox and to ascertain the opinion of parents regarding the usefulness of vaccination. DESIGN: Retrospective postal survey. SETTING: Province of Quebec. PARTICIPANTS: Random sample of 3333 families with children aged six months to 12 years. OUTCOME MEASURES: For cases of chickenpox that occurred between September 1, 1997 and August 31, 1998, the use of health services, time away from school or work, patient care required, direct and indirect costs for the families and the health care system, and the opinion of parents regarding chickenpox and the vaccine were evaluated. RESULTS: The response rate was 64.7%, and 18.8% of households reported a history of chickenpox, a total of 693 cases. A physician was consulted in 45.8% of these cases, and medication was used in 91.7%. The frequency of hospitalizations was 0.6%. Time away from work or school caused by the disease was 4.1 days on average, with 46.5% of absences being attributed to the risk of contagion. The total average cost of a case of chickenpox was $225. Direct expenses for households accounted for 11% of the total cost, public sector direct costs 7%, indirect costs related to absence from work 38% and caregiving time 45%. A majority of parents (70%) were in favour of a systematic childhood immunization program. CONCLUSIONS: Chickenpox without complications is disruptive for families, but the direct costs for families and the public sector are relatively small.